Dilating dangerous pupils. Issue 8 (August 1977) - Mapstone, R
Abstract : Altogether 85 eyes from patients at risk to the development of closed-angle glaucoma were dilated with either parasympatholytic or sympathomimetic drugs. Of 21 eyes dilated with cyclopentolate 1/2%, 9 developed angle closure and a significantly raised pressure at some stage during dilatation and subsequent miosis. Of 58 eyes dilated with tropicamide 1/2%, 19 developed angle closure and a significantly raised pressure during dilatation. Treatment with intravenous acetazolamide and pilocarpine rapidly returned pressure to normal levels. Six eyes that had previously had a positive provocative test with simultaneous pilocarpine and phenylephrine were safely dilated with phenylephrine alone. Subsequent miosis with pilocarpine produced closed-angle glaucoma in all eyes. The significance of these observations is explained and discussed, and it is suggested that high-risk eyes should never be dilated with cyclopentolate. Tropicamide is safe if elementary precautions are observed. Safest of all, however, is phenylephrine-induced mydriasis and subsequent miosis with thymoxamine drops 1/2%.